Cognitive approach to defining the contents, presentation, and formation of modern enterprise strategy - Ковтун, Олег Іванович (Technology audit and production reserves, 2013)
An interpretation of the enterprise strategy as a frame of a long-term behavioral pattern in the dynamic market environment is proposed and substantiated. The presented strategy interpretation eclectically combines different viewpoints on strategy and its various aspects-characteristics. The strategy is depicted as a certain whole system of support of decision-making, with organically synthesized and cognitively combined potential, discrete (multilevel, multivector) components that describe the core problematics, specifically the key aspects of functioning and development of an enterprise in a long-term period. They (specific, possible ways of solving the problems of the strategic context of an enterprise) are generated within the frame in the process of cognitive apprehension and mapping of available, feasible, and desired, for a given enterprise, competencies (factors of success), which essentially are the objects of strategic analysis, and are offered (depicted) in the frame-strategy as strategic alternatives (SA) of the behavior, decisions, and actions for certain stereotypical situations. In such case, the strategy attains the form of a frame process of decision making regarding the core aspects of functioning and development of an enterprise at all its levels and all its subsystems in a long-term period.